Childhood central adiposity at ages 5 and 9 shows consistent relationship with that of the maternal grandmother but not other grandparents. Issue 12 (9th May 2018) - Somerville, R.; Khalil, H.; Segurado, R.; Mehegan, J.; Viljoen, K.; Heinen, M.; Murrin, C.; Kelleher, C. C.
Summary: Background: The importance of a life course approach to childhood obesity has been emphasized; however, few studies can prospectively investigate relationships in three‐generation families. Objective: To prospectively investigate the relationship between grandparental and grandchild waist circumference (WC) at ages 5 and 9 down maternal and paternal lines. Methods: At baseline in the Lifeways Cross‐Generation Cohort, 1094 children were born to 1082 mothers; 585 were examined at age 5 and 298 at age 9. Of the total 589 children with measured WC, data were also available from 745 grandparents. Child WC was standardized for age and sex, and theory‐based hierarchical linear regression was used. Results: Maternal grandmother (MGM) WC was predictive of grandchild WC at both time points. At age 5, grandchild's standardized birth weight (B = 0.266, p = 0.001), mother's means tested eligibility for free medical care (B = 1.029, p = 0.001) and grandchild seeing maternal grandparents daily (B = 0.312, p = 0.048) were significant alongside MGM WC (B = 0.015, p = 0.019). At age 9, only MGM WC (B = 0.022, p = 0.033) and mother's WC (B = 0.032, p = 0.005) were significant. Mediation analysis with mother's WC showed significant direct relationship of MGM and grandchild WC. Conclusions: This prospective cross‐generational cohort shows consistent patterns of association between MGM and grandchild WC, not seen in other grandparental lineages.